La nic 2 y su incidencia en las empresas comerciales asociadas a la cámara de comercio, cantón Quevedo, año 2012. - Romero Solís, Horly David (2015)
Whereas all businesses require the establishment of an inventory system, it periodically allows the activities carried out by commercial companies associated with the Chamber of Commerce of Quevedo, being institutions that sell products, these require compliance with accounting standards and those principles that contribute to good management. Using the following methods: inductive, deductive, descriptive, analytical and applying the respective surveys, interviews with 185 associated companies resulting that they did not make a work plan for the implementation of IAS 2; so therefore only 21.08% of the companies studied differences between current accounting policies include the 70.81% of respondents said they did not generate reports regarding the financial statements under IAS 2, and in turn 45.57% of respondents said they have not made an equity reconciliation by the lack of training regarding this ledger account. As a result of analysis of the procedures required for the implementation of IAS 2 companies studied was determined that in the case of Madoba Company must include all expenses that are part of the cost to the sales price. In the case of the company OFIMODULOS SA being a company that manufactures furniture recording accounting entries is recommended while this product is in progress. In the application of administrative and accounting policy research led to results identify the lower of cost and estimated selling price according to net realizable value, this criterion applies when the purchase is made in cash or under the portal procurement and according to the Standard, the cash discounts are recognized with a reduction of the acquisition cost of the merchandise has been sold. This information is required to ensure that all member companies to understand and compare financial information from a single, understandable way.